Genetic depletion of adipose-derived Isthmin-1 causes hepatic steatosis - Saranya C. Reghupaty; Laetitia Coassolo; Meng Zhao; Ramya Lakshmi Narasimhan; Aayan Patel; Jameel Lone; Ewa Bielczyk-Maczynska; Niels B. Danneskiold-Samsoee; Taylor Brown; Zewen Jiang; Veronica L. Li; Katrin J. Svensson (Molecular Metabolism)
Objectives: Adipose tissue plays a critical role in obesity, as its dysfunction can impair lipid homeostasis and result in lipid overflow and ectopic lipid deposition in the liver. We previously demonstrated that Isthmin-1 (Ism1) regulates glucose uptake into the adipose tissue and suppresses hepatic steatosis, but the role of adipose-derived Ism1 is unknown. Here, we investigate the role of adipose-derived Ism1 in metabolic health and its impact on hepatic steatosis and lipid metabolism. Methods: In this study, we employed both a genetic knockout approach, selectively deleting Ism1 in adipose tissue of mice (AdipoQ-Ism1-KO), and a pharmacological approach by administering recombinant Ism1 protein to mice. These mice were subjected to a high fat-high fructose diet to simulate conditions that promote Metabolic-dysfunction Associated Steatotic Liver Disease (MASLD). Results: AdipoQ-Ism1-KO are of normal weight, but prone to severe hepatic steatosis in response to high fat-high fructose feeding. Lipidomic profiling through untargeted analyses in both gain-of-function and loss-of-function models was used to assess changes in hepatic lipid homeostasis. These results provide in vivo genetic support for the role of Ism1 as a regulator of the adipose–hepatic axis. Conclusions: Collectively, these data demonstrate that loss of adipose-derived Ism1 disrupts lipid homeostasis and accelerates the development of hepatic steatosis. This study provides a genetic basis for Ism1's involvement in metabolic regulation, suggesting a potential therapeutic target for treating metabolic disorders.